2020
DOI: 10.3126/ajms.v11i1.26500
|View full text |Cite
|
Sign up to set email alerts
|

The effect of supplementation of Lactobacillus paracasei HII01 on salivary cortisol, and dehydroepiandrosterone sulfate (DHEA-S) levels

Abstract: Background of the study: Fatigue is one of the serious health issues, and stress is the main factor that induces chronic fatigue syndrome (CFS). The dysregulation of stress management pathway may account for the development of CFS. The human body comprises several neurobiological networks to manage physical and emotional insults. Hypothalamic-pituitary- adrenal (HPA) axis is one of the important neuroendocrine networks involved in the neurophysiological activity of the host system. The response of HPA axis dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
1
1
1
Order By: Relevance
“…Our meta-analysis revealed no beneficial effect for probiotic consumption on cortisol level, which is in agreement with previous works. [1,3,17] In contrast to our findings, Lalitsuradej et al [33] reported that 12 weeks of probiotic supplementation (L. paracasei HII01) decreased salivary cortisol. Similarly, Messaoudi et al [34] and Sawada et al [35] also indicated that probiotic supplementation could attenuate urine free cortisol and salivary cortisol levels.…”
Section: Discussioncontrasting
confidence: 99%
“…Our meta-analysis revealed no beneficial effect for probiotic consumption on cortisol level, which is in agreement with previous works. [1,3,17] In contrast to our findings, Lalitsuradej et al [33] reported that 12 weeks of probiotic supplementation (L. paracasei HII01) decreased salivary cortisol. Similarly, Messaoudi et al [34] and Sawada et al [35] also indicated that probiotic supplementation could attenuate urine free cortisol and salivary cortisol levels.…”
Section: Discussioncontrasting
confidence: 99%
“…The absence of a PB effect on baseline measures before the animals were exposed to stress, however, suggest that probiotics may be more advantageous in psychologically challenging circumstances than in less stressful conditions ( Papalini et al, 2018 ). These results corroborate recent findings indicating that Lactobacillus paracasei H1101 decreased the salivary CORT/DHEA metabolites in humans ( Lalitsuradej et al, 2020 ), suggesting that the results have potential for translational relevance. Thus, the current endocrine findings provide additional support that the gut microbiome may play a regulatory role in the stress response ( Karl et al, 2018 ), providing a potential therapeutic window for the treatment of stress-related psychiatric illnesses.…”
Section: Discussionsupporting
confidence: 91%
“…We measured salivary cortisol, α-amylase ( 50 ), immunoglobulin A (IgA) ( 51 ), lactoferrin ( 52 ), and lysozyme ( 51 ) levels since they were found to be related to stress and anxiety. A recent study showed that the injection of probiotics for 12 weeks significantly reduced the level of salivary cortisol in nine fatigue subjects ( 53 ). Salivary α-amylase, IgA, lactoferrin, and lysozyme levels were measured by enzyme-linked immunosorbent assay kits (Immuno-Biological Laboratories, Inc., USA; Germany; and Assaypro LLC, USA).…”
Section: Methodsmentioning
confidence: 99%